Extreme ionization of heavy atoms in solid-density plasmas by relativistic second-harmonic laser pulses - Hollinger, R. (2020)
Stripping heavy atoms in solid matter of most of their electrons requires the extreme conditions that exist in astrophysical plasmas, but are difficult to create in the laboratory1–3. Here we demonstrate solid-density gold plasmas with atoms stripped of up to 72 electrons (N-like Au72+) over large target depths. This record ionization is achieved by irradiating solid foils and near-solid-density nanowire arrays with highly relativistic (3 × 1021 W cm−2) second-harmonic femtosecond laser pulses of '10 J energy focused into a 1.6 µm spot. The short wavelength and high intensity enable the interaction to occur at a relativistic critical density4,5 of 1023 cm−3. Solid targets reach a higher average charge in 1- to 2-µm-thick layers, while the less dense nanowire plasmas are heated to much larger depths ('8 µm) by energetic electrons generated near the nanowire tips. Larger laser spots could result in solid Au plasmas ionized up to He-like.